Sistem Informasi Geografis Apotek di Kotawaringin Timur Berbasis Web - Ramadhani, Nur Rachmat Fajar; Prasetyaningrum, Eka; Bachtiar, Lukman (Building of Informatics, Technology and Science (BITS), 2020)
Geographical Information System is an information system that is specialized in processing data that has spatial information (spatial reference). In a narrower sense, a Geographical Information System is a computer system that has the ability to build, store, manage and display geographic information, for example, data that is identified according to its location in a database. The purpose of this geographic information system is to find out information on the location of the distribution of pharmacies and drug data information in East Kotawaringin, so as to help people and people who are not native to East Kotawaringin. The development of a web-based pharmacy geographic information system in East Kotawaringin uses the programming language PHP and MySQL as the database system.